Assessment of knowledge & practice of Birth Preparedness and Complication Readiness among ASHAs - A pilot study - Annapurna Kari; Mubashir Angolkar (Elsevier, 2021)
Background: Maternal mortality is a substantial burden in developing countries. Birth Preparedness and Complication Readiness (BPRC) is an intervention included by WHO as an essential element of the antenatal care package. It is based on the premise that preparing for birth and being ready for complications reduces all three phases of delays in - identifying complications and deciding to seek care, identifying and reaching a health facility and receiving adequate and appropriate treatment at the health facility. Objective: To assess the knowledge and practice of Birth Preparedness and Complication Readiness among ASHAs. Method: ology: A pilot study was conducted on ASHAs of Mutaga Primary Health Centre (PHC), Belagavi Rural Area. All (28) ASHAs were included in the study. Informed consent was obtained after explaining about the study. Data regarding Knowledge and Practice towards Birth Preparedness and Complication Readiness (BPRC) was collected using a standard, pre-designed questionnaire by JHPIEGO. Results: The findings of the study revealed that 71.42%, 96.42% and 92.85% of ASHAs were knowing about severe bleeding which is one of the key danger signs during pregnancy, labour and postpartum period respectively. Knowledge of ASHAs regarding swollen hands/face which is another key danger sign was around 42.85%. About 32.14% of ASHAs were knowing about blurred vision during pregnancy. Less than 50% of the ASHAs were having knowledge about other danger signs. ASHAs had good knowledge about components of Antenatal care (ANC) but less than 25% of ASHAs were knowing BPCR as a component of ANC. Conclusion: Knowledge of ASHAs about the components and practice of BPCR was poor. Hence need of the hour is to train ASHAs regarding components of BPCR.